Discovery and validation of a novel blood‐based molecular biomarker of rejection following liver transplantation. Issue 8 (25th May 2020) - Levitsky, Josh; Asrani, Sumeet K.; Schiano, Thomas; Moss, Adyr; Chavin, Kenneth; Miller, Charles; Guo, Kexin; Zhao, Lihui; Kandpal, Manoj; Bridges, Nancy; Brown, Merideth; Armstrong, Brian; et al.
Abstract : Noninvasive biomarker profiles of acute rejection (AR) could affect the management of liver transplant (LT) recipients. Peripheral blood was collected following LT for discovery (Northwestern University [NU]) and validation (National Institute of Allergy and Infectious Diseases Clinical Trials in Organ Transplantation [CTOT]‐14 study). Blood gene profiling was paired with biopsies showing AR or ADNR (acute dysfunction no rejection) as well as stable graft function samples (Transplant eXcellent—TX). CTOT‐14 subjects had serial collections prior to AR, ADNR, TX, and after AR treatment. NU cohort gene expression (46 AR, 45 TX) was analyzed using random forest models to generate a classifier training set (36 gene probe) distinguishing AR vs TX (area under the curve 0.92). The algorithm and threshold were locked and tested on the CTOT‐14 validation cohort (14 AR, 50 TX), yielding an accuracy of 0.77, sensitivity 0.57, specificity 0.82, positive predictive value (PPV) 0.47, and negative predictive value (NPV) 0.87 for AR vs TX. The probability score line slopes were positive preceding AR, and negative preceding TX and non‐AR (TX + ADNR) ( P  ≤ .001) and following AR treatment. In conclusion, we have developed a blood biomarker diagnostic for AR that can be detected prior to AR‐associated graft injury as well a normal graft function (non‐AR). Further studies are needed to evaluate its utility in precision‐guided immunosuppression optimization following LT. Abstract : This study reports on a novel peripheral blood gene signature intended to distinguish acute rejection from other causes and healthy graft function in liver transplant recipients and provide early detection to inform and enhance immunosuppression management.